2021
DOI: 10.1186/s13287-021-02182-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved human adipose-derived stromal vascular fraction maintains fracture healing potential via angiogenesis and osteogenesis in an immunodeficient rat model

Abstract: Background Novel therapeutic strategies for the healing of nonunion, which has serious effects on the quality of life of patients, are needed. We evaluated the therapeutic effect of local transplantation of human stromal vascular fraction (SVF) cells on fracture healing in a rat non-healing fracture model and compared the effects between freshly isolated (F) and cryopreserved (C)-SVFs. Methods Non-healing fracture model was induced in the femur of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Obviously, the translational potential of frozen SVF would dramatically increase if it is equally effective as freshly isolated cells. Consistent with a prior study that showed comparable bone healing via angiogenesis using fresh or frozen SVF [37], our results showed that either fresh (Fig. 2, 2, 3) or frozen SVF (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Obviously, the translational potential of frozen SVF would dramatically increase if it is equally effective as freshly isolated cells. Consistent with a prior study that showed comparable bone healing via angiogenesis using fresh or frozen SVF [37], our results showed that either fresh (Fig. 2, 2, 3) or frozen SVF (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…ADSCs and the SVF also downregulated chondrocyte MMP‐13 mRNA expression levels. The paracrine effect of ADSCs and SVF on cell viability, promotion of anabolic factors, and inhibition of catabolic factors of chondrocytes has been demonstrated previously (Kamenaga et al, 2021; Kuroda et al, 2019). Several authors compared the therapeutic effect of ADSCs with SVFs for nerve regeneration, hypertrophic scar remodeling, treatment of acute myocardial infarction, and cartilage regeneration in animal models, where an almost equal effect was usually observed (Domergue et al, 2016; Shimizu et al, 2018; van Dijk et al, 2011; You et al, 2015).…”
Section: Discussionmentioning
confidence: 53%
“…ADSCs and the SVF also downregulated chondrocyte MMP-13 mRNA expression levels. The paracrine effect of ADSCs and SVF on cell viability, promotion of anabolic factors, and inhibition of catabolic factors of chondrocytes has been demonstrated previously (Kamenaga et al, 2021;Kuroda et al, 2019).…”
Section: Pellet Coculturementioning
confidence: 94%
“…Exosome content was also higher in the non-enzymatic processed human adipose tissue [ 126 ]. Using enzymes for SVF isolation however may cause a severe inflammatory response, massive lymphocyte infiltration, neovascularization, and cartilage destruction after in vivo administration [ 127 , 128 ]. AD-tSVF was reported to be safe, less costly, and less time consuming [ 129 ].…”
Section: Adipose Derived Stromal Vascular Fraction (Ad-svf)mentioning
confidence: 99%